ENHANCING THE ACCURACY OF LOW‐FREQUENCY BEHAVIOR DATA COLLECTION BY DIRECT‐CARE STAFF. (11th September 2013) - Reis, Melanie H.; Wine, Byron; Brutzman, Brian
<x xml:space="preserve">Abstract</x> Accurate data collection on low‐frequency problem behavior is imperative given the paucity of opportunities to observe, record, and assess responding. Infrequently occurring behavior also provides a challenge for staff training relative to data collection. The present study evaluated the use of task clarification and feedback to teach direct‐care staff members to take data on recorded, simulated problem behavior. Results indicated that the procedures were effective in increasing accuracy not only in the contrived scenarios but also for problem behavior in the natural environment. These data suggest that task clarification and feedback on simulated problem behavior may be an effective method to increase accurate data collection on problem behavior in the natural environment. Copyright © 2013 John Wiley & Sons, Ltd.